Risk perception of compound emergencies: A household survey on flood evacuation and sheltering behavior during the COVID-19 pandemic. (July 2023) - Sohn, Wonmin; Kotval-Karamchandani, Zeenat
Highlights: Two survey-based choice models predicted disaster survivors' emergency responses. Compound risks modified the elderly's traditional evacuation choices. Lack of mask enforcement reduced evacuees' likelihood of long-term sheltering. Emergency responses were socio-demographically characterized. Democrats, females, and the unemployed showed greater concern about virus exposure. Abstract: Compound hazards are derived from independent disasters that occur simultaneously. Since the outbreak of COVID-19, the coupling of low-probability high-impact climate events has introduced a novel form of conflicting stressors that inhibits the operation of traditional logistics developed for single-hazard emergencies. The competing goals of hindering virus contagion and expediting massive evacuation have posed unique challenges for community safety. Yet, how a community perceives associated risks has been debated. This research utilized a web-based survey to explore the relationship between residents' perceptions of conflicting risks and emergency choices made during a historic compound event, the flooding in 2020 in Michigan, US that coincided with the pandemic. After the event, postal mail was randomly sent to 5, 000 households living in the flooded area, collecting 556 responses. We developed two choice models for predicting survivors' evacuation options and sheltering length. The impact of sociodemographic factors on perceptions of COVID-19 risks was also examined. The results revealed greater levels of concern among females, democrats, and the economically inactive population. The relationship between evacuation choice and concern about virus exposure was dependent upon the number of seniors in the household. Concern about a lack of mask enforcement particularly discouraged evacuees from extended sheltering.